ANALISIS BIAYA DAN KEUNTUNGAN USAHA KAMBING PERANAKAN ETAWA (PE) DI IKHSAN FARM DESA SEI GLUGUR KECAMATAN PANCUR BATU - Muhammad Apriandi; Media Agus Kurniawan (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the costs and benefits of Etawa crossbreed (PE) goat farming business at Ikhsan Farm, Sei Glugur Village, Pancur Batu District. The Etawa crossbreed (PE) goat farming business has great potential, both as a producer of meat and milk, but challenges in maintenance management and breeding programs can affect productivity levels. This study uses a quantitative descriptive approach, with a financial feasibility analysis method through the calculation of the R/C (Total Revenue Cost Ratio) = TR/TC ratio to assess the efficiency of costs and benefits of the goat farming business. The results of the analysis show that the Etawa crossbreed (PE) goat farming business at Ikhsan Farm is financially feasible to be developed with an R/C ratio of 2.18> 1, which indicates promising benefits for farmers. This study provides an overview of the importance of efficient management to improve the sustainability of the Etawa crossbreed (PE) goat farming business.